Repression of Fyn-related kinase in breast cancer cells is associated with promoter site-specific CpG methylation - Bagu, Edward T. (Oncotarget, 2017)
The triple-negative breast cancer subtype is highly aggressive and has no defined therapeutic target. Fyn-related kinase (FRK) is a non-receptor tyrosine kinase, reported to be downregulated in breast cancer and gliomas, where it is suggested to have tumor suppressor activity. We examined the expression profile of FRK in a panel of 40 breast cancer cells representing all the major subtypes, as well as in 4 non-malignant mammary epithelial cell lines. We found that FRK expression was significantly repressed in a proportion of basal B breast cancer cell lines. We then determined the mechanism of suppression of FRK in FRK-low or negative cell lines. In silico analyses of the FRK promoter region led to the identification of at least 17 CpG sites. Bisulphite sequencing of the promoter region revealed that two of these sites were consistently methylated in FRK-low/negative cell lines and especially in the basal B breast cancer subtype. We further show that treatment of these cells with histone deacetylase inhibitors, Entinostat and Mocetinostat' promoted re-expression of FRK mRNA and protein. Further, using luciferase reporter assays, we show that both GATA3-binding protein FOG1 and constitutively active STAT5A increased the activity of FRK promoter. Together, our results present the first evidence that site-specific promoter methylation contributes to the repression of FRK more so in basal B breast cancers. Our study also highlights the potential clinical significance of targeting FRK using epigenetic drugs specifically in basal B breast cancers which are usually triple negative and very aggressive.